High-Energy Transsyndesmotic Ankle Fracture Dislocation—Injury Characteristics, Radiographic Outcomes, and Factors Affecting the Rate of Posttraumatic Arthritis in Logsplitter Injuries. Issue 3 (March 2022) - Sidhu, Sahil Prabhnoor; Atwan, Yousif; Cavanagh, Joseph; Sidhu, Veer Sohail; Del Balso, Christopher; Schemitsch, Emil H.; Sanders, David W.; Lawendy, Abdel R.
Abstract : Objectives: To investigate patient demographics, injury characteristics, radiographic outcomes, and identify risk factors for developing posttraumatic arthritis in high-energy transsyndesmotic ankle fracture dislocations or "logsplitter" injuries. Design: Retrospective cohort study. Setting: Academic level one trauma center. Patients/Participants: Twenty-seven adult patients with logsplitter injuries. Intervention: All patients were treated with open reduction internal fixation, with possible addition of syndesmosis screw(s) and deltoid repair. Main Outcome Measurements: The rate of posttraumatic arthritis at one year along with rate and reasons for reoperation. Results: Twenty-seven patients were included with a mean follow-up of 14.5 ± 12.5 months. At one-year postoperative, 14 of the 20 patients (70%) demonstrated posttraumatic arthritis. Two patients (7.4%) went onto fusion. The reoperation rate was 51.9%. There was no significant difference in the arthritis rate with the number of syndesmosis screws used, quality of reduction, or addition of deltoid repair. Conclusions: The logsplitter injury is one with devastating outcomes and high rates of arthritis; it should be considered separately from conventional ankle fractures. The role of deltoid repair remains unclear. Further study of this injury pattern is required. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.